The Occurrence of Veterinary Pharmaceuticals in the Environment: A Review - Kaczala, Fabio; E. Blum, Shlomo (Current Analytical Chemistry, 2016)
It is well known that there is a widespread use of veterinary pharmaceuticals and consequent release into different ecosystems such as freshwater bodies and groundwater systems. Furthermore, the use of organic fertilizers produced from animal waste manure has been also responsible for the occurrence of veterinary pharmaceuticals in agricultural soils. This article is a review of different studies focused on the detection and quantification of such compounds in environmental compartments using different analytical techniques. Furthermore, this paper reports the main challenges regarding veterinary pharmaceuticals in terms of analytical methods, detection/quantification of parent compounds and metabolites, and risks/toxicity to human health and aquatic ecosystems. Based on the existing literature, it is clear that only limited data is available regarding veterinary compounds and there are still considerable gaps to be bridged in order to remediate existing problems and prevent future ones. In terms of analytical methods, there are still considerable challenges to overcome considering the large number of existing compounds and respective metabolites. A number of studies highlight the lack of attention given to the detection and quantification of transformation products and metabolites. Furthermore more attention needs to be given in relation to the toxic effects and potential risks that veterinary compounds pose to environmental and human health. To conclude, the more research investigations focused on these subjects take place in the near future, more rapidly we will get a better understanding about the behavior of these compounds and the real risks they pose to aquatic and terrestrial environments and how to properly tackle them.
Keywords: Animal husbandry